Representing the Humanistic Face of Pancasila Through the Virtue Volunteer Movement - Galuh Ibrahim; Encep Syarief Nurdin; Yadi Ruyadi; Mupid Mupid; Salsyabila Ika Putri Aryaningrum (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The Pancasila-inspired humanitarian volunteer movement represents a tangible form of ideology realization in Indonesian society. This article explores the strategic role of volunteers as change agents who revive the spirit of mutual cooperation, deliberation, and social justice amidst growing societal complexity. From the perspective of Pancasila, volunteering is not merely a social activity but an ideological praxis rooted in national values. Adopting a humanist approach, this paper highlights the contribution of volunteers as intermediaries between the government and the people, while also promoting inclusive democratic participation. It further addresses the challenges and strengthening strategies for Pancasila-based volunteer movements in the context of globalization and the digital era. Cross-sector collaboration and community-based education are crucial to sustain this movement as a foundation for national character development.